Enhancing Science Education Through Laboratory-Based Learning in Secondary Schools in Nepal - Tamrakar, Pratima; Timilsna, Narayan Prasad; Devkota , Krishna Maya (Educational Journal, 2025)
The study assessed the pull and push factors influencing the Laboratory Teaching Method compared to the traditional lecture method on learning science. Employing a mixed-method research design, the study has collected quantitative data from achievement tests of experimental and control groups, alongside qualitative data from interviews with teachers and students. Analysis revealed a significant difference in the achievement levels, with a t-value of 12.388 for the experimental group. It indicates that the laboratory method enhanced students' utilization skills and adoption of behavior with practical knowledge and information. However, qualitative findings highlighted challenges encountered by both teachers and students in implementing this method. Addressing these challenges is essential for further improving student outcomes in science education, underlining the necessity of innovative pedagogies in teaching.